Hubungan Antara Indeks Massa Tubuh dengan Kadar Asam Urat di Ruang Azziziah Rumah Sakit Umum an Nisaa Kabupaten Blitar - Eni Kusriati; Byba Melda Suhita (Journal of Health Science Community, 2022)
Uric acid is a compound in the human body, with a normal ratio of 3-7.2mg/dL for males and women 2-6mg/dL. If the excess (hyperuricemia) levels of uric acid in the blood plasma will be an indication of disease in the human body. Several factors that influence the increase in uric acid concentration (hyperuricemia) is a high diet which is characterized by a high body mass index value (obesity). This study aims to determine the relationship between body mass index and blood uric acid levels at An-Nisaa General Hospital. This study uses a purpose sampling technique commonly used in scientific research by determining certain criteria. The population in this study were inpatients in the Azziziah Room at RSU An-Nisaa Blitar who were more than 50 years old with a research sample of 32 respondents. The results showed that the level of uric acid levels of inpatients in the Azziziah Room at RSU An-Nisaa Blitar was 6.46 on average and body mass index was 24.39 on average. The results of statistical tests using the Pearson product moment test obtained a significant relationship with p value (0.004) less than α, so there is a relationship between blood uric acid levels and body mass index with a correlation value of 0.491 which is interpreted as the strength of the relationship between variables in moderate level with a positive relationship direction.Patients are advised to maintain a diet by avoiding fatty foods and have high purine levels.